Impact of the Integration of Text-Messaging in Mathematics Teaching-Learning Process (Global Journal of Management and Business Research, 2015)
This research study established the impact of the integration of text-messaging in Mathematics teaching-learning process This one shot design study employed the Pre-Post Test method of investigation After the students took the Pre-Test the integration of text-messaging in the teaching-learning process was done for two weeks At the end of the two-week allotment of the lesson the students took the Post-Test and were surveyed on their attitude towards the integration of text-messaging It was found out that the Post-Test result is higher than the Pre- Test result Alpha 0 05 Furthermore the students agreed on the integration of text-messaging in the teaching-learning process
Keywords: text-messaging; mathematics teaching-learning process; university of san carlos; impact study; mobile gadget